Surgical outcomes following mitral valve surgery - C Rergkliang; A Chetpaophan; V Chittithavorn; P Vasinanukorn (Journal of Health Science and Medical Research (JHSMR), 2005)
Objective: To report the surgical outcomes after mitral valve surgery at Songklanagarind Hospital Material and Methods: The medical records of all patients who underwent mitral valve surgery between January 2001 and December 2003 at Songklanagarind Hospital were reviewed. The following data was examined: preoperative clinical characteristics, echocardiographic reports, operative technique, postoperative course and short-term clinical outcomes. Results: There were 122 patients, with a mean age of 38.17 ± 15.73 years (range 10-72 years). The New York Heart Association classes (NYHA class) I, II, III and IV were 2 (1.6%), 36 (29.5%), 57 (46.7%) and 27 (22.1%), respectively. 1M.D., Assist. Prof., 2M.D. Lecture Division of Cardiovascular and Thoracic Surgery, Department of Surgery, Faculty of Medicine, Prince of Songkla University, Hat Yai, Songkhla, 90110, Thailand Seventy-one patients (58.2%) had atrial fibrillation and 51 (41.8%) had sinus rhythm. Mitral stenosis was predominant in our patients (53.3%), and the most common etiology was rheumatic heart disease (84.4%). Mitral valve replacement was the most common procedure (64.8%). The 30-day mortality rate was 2.4% (3 patients). The mean follow-up was 10.89 ± 5.08 months (range 4-32 months) and there were 2 deaths during follow-up. Most of the survivors were in NYHA class I (85%). Conclusion: We achieved a good surgical outcome in mitral valve surgery from our initial experience.